Extended first‐principles molecular dynamics simulations of hot dense boron: equation of state and ionization. Issue 10 (8th April 2022) - Blanchet, Augustin; Soubiran, Francois; Torrent, Marc; Clérouin, Jean
Abstract: The extended first‐principles molecular dynamics (Ext. FPMD) model introduced by Shen Zhang et al. has been implemented within the ab initio DFT software package ABINIT and is now publicly available. This model allows performing quantum molecular dynamics simulations (QMD) at high temperatures bypassing the well‐known orbitals wall . QMD simulations can be done smoothly in the full range of temperatures from cold condensed matter to hot plasmas (>100 eV) passing by the warm dense matter regime. At high temperature, a minimum of Kohn‐Sham orbitals is kept, allowing for deep ionization effects to manifest, such as the Schottky anomaly of the specific heat, in contrast with orbital‐free approaches for which this effect is absent. Using the new 9.6 ABINIT version, we present extensive simulations of boron along isochores, from a few Kelvins to thousands of eVs, in the Gigabar regime and construct a table. The Hugoniot curve is found in close agreement with the FPEOS model, for a much lower computational intensity. An ionization analysis, deduced from the pressure or from the structure, emphasizes the crucial contribution of the very deep 1 s shell in the maximum compression regime.